2020
DOI: 10.1002/asi.24368
|View full text |Cite
|
Sign up to set email alerts
|

Saving social media data: Understanding data management practices among social media researchers and their implications for archives

Abstract: Social media data (SMD) offer researchers new opportunities to leverage those data for their work in broad areas such as public opinion, digital culture, labor trends, and public health. The success of efforts to save SMD for reuse by researchers will depend on aligning data management and archiving practices with evolving norms around the capture, use, sharing, and security of datasets. This paper presents an initial foray into understanding how established practices for managing and preserving data should ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Social media users share sensitive and highly personal information, but it is unclear whether they are aware that their data may be used for scientific research (Hemphill et al , 2021). Such users might feel very uncomfortable once they learn that their data were collected and used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media users share sensitive and highly personal information, but it is unclear whether they are aware that their data may be used for scientific research (Hemphill et al , 2021). Such users might feel very uncomfortable once they learn that their data were collected and used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Machine learning, computer vision, and social media studies often use "found" data [Hemphill et al 2021;Jo and Gebru 2020;Paullada et al 2021] and render curatorial decisions such as "what data should be available, " "in which format(s) should data be provided, " or "how should this data be sampled" invisible. For instance, datasets scraped from the web (such as Flickr photos [Scheuerman et al 2021;Zhang et al 2015] or Wikipedia talk pages [Wulczyn et al 2016[Wulczyn et al , 2017) suffer from biases in representation [Jo and Gebru 2020].…”
Section: What Renders Data Curation Invisible?mentioning
confidence: 99%
“…It is possible to identify many reasons that triggered such debates on existing infrastructures. One factor lies in the vast amounts of data and metadata produced in the course of today's dataintensive science (Corujo;Silva;Revez, 2016;Hemphill;Leonard;Hedstrom, 2020). This boom in value is paired with an increase in the variety of formats and representations, which, by itself, complicates the mission of interoperability, understood as "[…] the ability of data or tools from noncooperating resources to integrate or work together with minimal effort" (Wilkinson et al, 2016, p. 2).…”
Section: Structure Of a Fair Accessormentioning
confidence: 99%